Distinct mutational landscapes and phylogenomic insights of the SARS-CoV-2 delta variant in Pakistan and India: Regional evolution, novel mutations, and epidemiological implications - Nazia Fiaz; Atia Basheer; Imran Zahoor; Saima Naveed; Tahir Yaqub (PLoS ONE, 2026)
Delta SARS-CoV-2 triggered a devastating wave of COVID-19 in India, infecting approximately 26% of the population (~357 million people) within four months, with ~0.4 million new cases per day, and around 250,000 reported deaths. In contrast, Pakistan experienced a much milder Delta wave, recording only 320,333 infections and 6,287 deaths. Against this epidemiological background, the current study aimed to identify genomic mutations in the delta-variant isolates reported from India and Pakistan and to compare their mutational profiles and phylogenomic patterns, without inferring direct clinical causality, in these neighboring countries. We analyzed 1,312 Pakistani and 3,140 Indian delta-variant genomes from the GISAID database to characterize their mutational spectrum and phylogenomic relationships in a global context. A total of 3,412 mutations were identified in Pakistani isolates compared with 6,856 mutations in Indian samples, reflecting differences in sample size, with NSP3 and spike protein emerging as the most frequently mutated regions. After normalization on a per-genome basis, Pakistani Delta genomes showed a slightly higher mutation density across most ORFs. Several globally common mutations, including ORF8: S84L, ORF1b: P1000L, and S: D157–158 deletions, were absent in both countries. Indian delta-genomes exhibited distinctive variants such as an M1M mutation in ORF7a and multiple stop-gain mutations in ORF3a, ORF7a, ORF8, ORF10, and NSP4, which may reflect population-specific evolutionary patterns rather than definitive effects on pathogenicity or transmissibility. In contrast, Pakistani isolates carried three novel missense mutations, NSP12b: Q348H, ORF6: K42E, and ORF3a: Y211H, at low prevalence. Phylogenomic analysis revealed that Pakistani isolates clustered primarily with Middle Eastern lineages, particularly from Saudi Arabia and Oman, suggesting international travel–linked introductions, rather than implying exclusive transmission routes. These findings highlight distinct regional evolutionary trajectories of delta-variant and demonstrate that differences in total mutation counts do not directly translate into per-genome mutational burden or disease severity. Our results emphasize the need for continued genomic surveillance to monitor region-specific viral adaptations and inform public health strategies.